SPICE implementation of a finite element method based model for bipolar power semiconductors - Armando Araújo (2003)
This paper describes the methodology associated with the practical implementation, in SPICE circuit simulator, of a Finite Element Method (FEM) based model developed for Bipolar Power Semiconductor (BPS) simulation. The methodology is based on a modular approach that associates each zone of the semiconductor to a subcircuit implemented into SPICE simulator. Modeling a semiconductor is based in the union of the set of subcircuit modules necessary to the different zones. Calculus of instantaneous distribution of lightly doped zones carriers (ambipolar diffusion equation (ADE) solution in space/time) is made with a group of subcircuit modules, analogue to FEM elements. The paper shows how each module is implemented and how easily elements with different sizes, topologies or physical properties are made. Remaining semiconductor zones (highly doped emitters narrow base and MOS zones) are modeled with subcircuits using classical approaches. Voltage drops are modeled with subcircuits implementing a Boltzmann approach for junctions and a Poisson approach for depletion zones. Description for obtaining each associated SPICE subcircuit is made. Global solution is approached by serial addition of these modules (each one directly related to one element of the domain). The paper concludes with simulations showing hole/electron distribution, in time/space, in low-doped zones of PIN Diodes, BJTs and IGBTs, as well as, corresponding dynamic commutation waveforms for current and voltage.